(3GdebJVH ef eKjQ GdZQGe Edi RjGQI GdbOS hGdTGes - (3eLghds; (3GHf gdGd GdebOSj , LeGd GdOjf CHh eMehO CMeO Hf eMeO Hf EHQGgje Hf gdGd GdNhGUj GdebOSj GdTGaYj, GHf gdGd GdebOSj,J (B765 (3g` s ((3eMeO Hf agO GdgGTei Gdeci s)
(3ChdgG (B:s
(3CeG HYO agPG GdcJGH fajSLYdJg Ydi bSejf GdbSe GdChd ai aVGFd GdTGe s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B224 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B160s
Keywords: (3GdJGQjNs